Perioperative Application of 2% Lidocaine - Dewi, Fitri Hapsari; Nugroho, Andy; Muttaqin, Fandi Ahmad (Faculty of Medicine, Brawijaya University, 2022)
Perioperative intravenous lidocaine (IVL) can help minimize opioid-related side effects that impede the postoperative recovery process. Neurological side effects were averaged at an 8 mg/kg dose, and cardiotoxicity side effects were reported at plasma values greater than 21 g/ml. Approximately 90% of lidocaine is converted to monoethylglycinexylidide (MEGX) in the liver via oxidative demethylation (dealkylation). Analysis of MEGX concentrations after lidocaine administration can be a method used to evaluate liver function. Perioperative intravenous lidocaine lowers discomfort, nausea, the duration of ileus, the need for opioids, and the length of time spent in the hospital after surgery. During injection, low blood concentrations can result in these symptoms, which may last for several hours or days after termination. Postoperative problems, such as pain and organ failure, can be caused by anti-inflammatory and pro-inflammatory components. Analgesic, anti-inflammatory, and anti-hyperalgesic are just some of the other effects of lidocaine. It also decreases the volume of the airways and the rate of breathing, prolongs the duration of exhalation, reduces the respiratory rate and tidal volume, also causes vasoconstriction at low concentrations and vasodilation at high concentrations. In clinical applications, lidocaine can prevent propofol injection pain, improve postoperative recovery, and play a role in various surgical procedures. Perioperative IVL application is proven to provide more benefits in various surgeries compared to other available anesthetic options. Very few studies have systematically analyzed the occurrence of side effects, and the quality of evidence is low.